Chemical of darkness (Melatonin): A ray of glow to dentistry - Vijayakumar Ambaldhage; Purnachandrarao N Naik; Ravi Kiran Alaparthi; Samatha Yelamanchili (Wolters Kluwer Medknow Publications, 2016)
Melatonin (MLT) is a neuroendocrine hormone secreted mainly by the pineal gland. Recent studies have shown that it is also synthesized in various other parts of the body including salivary glands. The most significant effects of MLT are because of its potent antioxidant, antiageing, immunomodulatory, shielding and antineoplastic properties. Because of these effects, it might be used therapeutically in dentistry for the potentially malignant disorders, lesions of mechanical, bacterial, fungal or viral origin. It stimulates synthesis of collagen fibers and bone formation, and can be used in postsurgical wounds caused by tooth extractions, periodontal therapies, and dental implants. Thus, it is important for the dental clinicians to be familiar with the possible therapeutic uses of MLT in dentistry. The aim of the present article is to review related articles in the literature that have focused on MLT and its applications in dentistry and to provide a quick sketch of applications of MLT in dentistry for dental clinicians. Our review concludes that the research to date certainly offers valid applications of MLT in dentistry. Meanwhile, practical strategies with the highest success rates are needed for further interventions.